A multicenter, double-blind, randomized trial on the bleeding profile of a drospirenone-only pill 4 mg over nine cycles in comparison with desogestrel 0.075 mg - Santiago Palacios; Enrico Colli; Pedro‐Antonio Regidor (2019)
Abstract Purpose A typical compliance problem in the use of traditional progestin-only pills is the irregular bleeding pattern and the strict daily intake. Desogestrel 75 mg has a 12-h missed-pill window; however, its poor cycle control limits a more common use. Methods A drospirenone (DRSP)-only pill was developed to improve the bleeding profile. Setting A phase III study in healthy women aged 18–45 years was performed to compare the bleeding profile and safety of a DRSP-only pill in a regime of 24 days of 4 mg of DRSP tablets followed by 4 days of placebo versus desogestrel 0.075 mg per day continuously over nine cycles. Population A total of 858 women with 6691 drospirenone and 332 women with 2487 desogestrel treatment cycles were analyzed. Main outcome measures The primary end point was the proportion of women with unscheduled bleeding/spotting in each cycle from cycles 2 to 9 and cumulative in cycles 2–4 and cycles 7–9. Results In each cycle, up to cycle 7, the proportion of women with unscheduled bleeding was statistically significantly lower in the DRSP group than in the DSG group ( p = 0.0001, Chi-square test). Conclusions This report describes the improvement in bleeding profile of women using the new DRSP-only oral contraceptive in comparison to DSG, providing a better quality of live and adherence to the contraceptive method. EudraCT Registration Number: 2011-002396-42.